2022
DOI: 10.1021/acsinfecdis.2c00395
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the Inhibitory Effect of Thiol Compounds and Demetallation Rates from the Zn(II) Active Site of Metallo-β-lactamases (IMP-1 and IMP-6) Associated with a Single Amino Acid Substitution

Abstract: Gram-negative bacteria producing metallo-β-lactamases (MBLs) have become a considerable threat to public health. MBLs including the IMP, VIM, and NDM types are Zn(II) enzymes that hydrolyze the β-lactam ring present in a broad range of antibiotics, such as N-benzylpenicillin, meropenem, and imipenem. Among IMPs, IMP-1 and IMP-6 differ in a single amino acid substitution at position 262, where serine in IMP-1 is replaced by glycine in IMP-6, conferring a change in substrate specificity. To investigate how this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…The bacterial strains used in this study, MBL-producing E. coli transformants and Enterobacterales , have been listed in our previous reports ( 11 , 45 ). The expression and purification of IMP-1, IMP-6, NDM-1, VIM-2, and SMB-1 were performed according to previously described methods ( 11 , 45 , 46 ).…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial strains used in this study, MBL-producing E. coli transformants and Enterobacterales , have been listed in our previous reports ( 11 , 45 ). The expression and purification of IMP-1, IMP-6, NDM-1, VIM-2, and SMB-1 were performed according to previously described methods ( 11 , 45 , 46 ).…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, resistance to β-lactam-BLI combinations has been identified both in the laboratory and clinical settings, including against avibactam and vaborbactam, even before their approval by the FDA [25][26][27]. Recent studies have demonstrated antibiotic resistance against combination therapies involving the latest BLIs and against new β-lactams, such as durlobactam [28], relebactam [29,30], zidebactam [31], tazobactam [32], taniborbactam [33], thiol-containing BLIs under development [34], and cefiderocol [35]. The resistance mechanisms include upregulation of efflux, mutations in the β-lactam target PBPs, and expression of β-lactamases and mutants less susceptible to the specific BLI, such as KPC-109 [36], NDM-9 [33], IMP-6 [34], and CMY-178 [37].…”
Section: Targeting β-Lactamases: Innovative Technologies and Promisin...mentioning
confidence: 99%
“…Recent studies have demonstrated antibiotic resistance against combination therapies involving the latest BLIs and against new β-lactams, such as durlobactam [28], relebactam [29,30], zidebactam [31], tazobactam [32], taniborbactam [33], thiol-containing BLIs under development [34], and cefiderocol [35]. The resistance mechanisms include upregulation of efflux, mutations in the β-lactam target PBPs, and expression of β-lactamases and mutants less susceptible to the specific BLI, such as KPC-109 [36], NDM-9 [33], IMP-6 [34], and CMY-178 [37]. These resistance mutants highlight the need for the antimicrobial field to constantly explore novel inhibitor chemotypes to counter future resistance.…”
Section: Targeting β-Lactamases: Innovative Technologies and Promisin...mentioning
confidence: 99%